A Rare Finding in Epilepsy: Ictal Singing and Spitting - Türk, Bengi Gül; Uzan, Mustafa; Özkara, Çiğdem (Cerrahpaşa Medical Journal, 2020)
Singing is an emotional musical vocalization, with several forms and styles in different cultures. Ictal singing in focal epilepsy is rare. It is accepted as a complex automatism, with only few reported cases. We reported a case with complex automatisms that included ictal singing and spitting, with an epileptogenic zone in the right temporal lobe. A 24-year-old right-handed man was referred for pharmacoresistant epilepsy. Despite administering three anticonvulsant drugs in efficient doses, seizures occurred several times per month. The seizures were characterized by staring for a few seconds, during which the patient stayed unresponsive. This was followed by spitting and singing, the same song each time. The song was from a television-drama series that he had watched during his childhood and had an emotional impact on him. Our patient sang the same song during every attack. The song was from a television series. The patient had watched the series during his childhood and was emotionally influenced with it. Therefore, it might be the release of subconscious emotions suppressed during childhood, which stimulated him to recall the song and sing it during the seizures. Cite this article as: Türk BG, Uzan M, Özkara Ç. A Rare Finding in Epilepsy: Ictal Singing and Spitting. Cerrahpaşa Medical Journal 2020; 44(2): 104-107.